2020
DOI: 10.1021/acs.macromol.0c01888
|View full text |Cite
|
Sign up to set email alerts
|

Periodically Spaced Side-Chain Liquid Crystalline Polymers

Abstract: The melt-transesterification polymerization of diethyl malonate derivatives bearing a pendant mesogen, with α,ω-alkanediols of varying lengths generated a series of side-chain liquid crystalline polymers, wherein the intervening backbone alkylene spacer segment was systematically varied; the effect of the backbone spacer segment on the liquid crystalline property was examined using differential scanning calorimetry (DSC), X-ray scattering, and polarizing light microscopic investigations. Two different mesogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…[44][45][46][47][48] Building on these studies, we recently began exploring the possibility of enhancing the folding propensity of PGACs by the inclusion of mesogenic aromatic units, such as biphenyl or azobenzene, either within the pendant segment or within the polymer backbone; the presence of the rigid aromatic mesogens, we expected, would not only serve to enhance the tendency to fold but would also permit us to examine the possibility of regulating the nature of the mesophase formed. In our previous report, we examined the influence of the nature and length of the backbone segment in periodically spaced side-chain LCPs; 49 the studies revealed that when alkylene segments were present in the backbone, only nematic mesophases were formed, even though smectic-type layering was evident in the solid state. However, when polar flexible PEG segments were present in the backbone, lowering of the melting temperature and segment immiscibility drove the formation of smectic mesophases.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47][48] Building on these studies, we recently began exploring the possibility of enhancing the folding propensity of PGACs by the inclusion of mesogenic aromatic units, such as biphenyl or azobenzene, either within the pendant segment or within the polymer backbone; the presence of the rigid aromatic mesogens, we expected, would not only serve to enhance the tendency to fold but would also permit us to examine the possibility of regulating the nature of the mesophase formed. In our previous report, we examined the influence of the nature and length of the backbone segment in periodically spaced side-chain LCPs; 49 the studies revealed that when alkylene segments were present in the backbone, only nematic mesophases were formed, even though smectic-type layering was evident in the solid state. However, when polar flexible PEG segments were present in the backbone, lowering of the melting temperature and segment immiscibility drove the formation of smectic mesophases.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis procedure of diethyl malonate based azobenzene mesogenic monomer bearing C6 spacer and C6 tail segment was described in our previous study. 1 Diethyl malonate based monomer of azobenzene bearing C10 spacer and C10 tail segment was synthesized following same procedure.…”
Section: Synthetic Procedures and Structural Elucidation Scheme 1: Sy...mentioning
confidence: 99%
“…For them a repeated bending of the main chain spacer between the mesogens (not straight spacer) is observed (Figure 4). [ 76–82 ]…”
Section: Smectic Main Chain Polymers With Special Side Chainsmentioning
confidence: 99%
“…This regularly bended structure allows now the incorporation of functional, even sterically demanding units as side groups, without disturbing the dense packing of the mesogens and thus without disturbing the LC ordering. [ 76–82 ] Concerning the smectic structure the smectic layer thickness includes the length of the side chains (Figure 4). In smectic elastomers prepared from these systems, the shape variation at the phase transition to the isotropic phase is well detectable, but much lower than in the case of LC‐main chain elastomers with a straight spacer.…”
Section: Smectic Main Chain Polymers With Special Side Chainsmentioning
confidence: 99%